Food Infections and Food Intoxications - Damon, Samuel Reed (Williams & Wilkins, 1928)
An overview of the etiology, symptoms, diagnosis, treatment, and prophylaxis of food poisoning. Content is divided into three sections: infections from food, intoxication from food, and zoo-parasitic infections acquired through food. Includes black and white print illustrations. Work is digitized in its entirety.
Keywords: Food poisoning; Medical parasitology; Diseases--Causes and theories of causation; Intoxication; Food science